Study on the Development of Secondary Vocational Education in China - Junfeng Fu (Ilmu Inovasi Nusantara, 2023)
In order to understand the current situation of secondary vocational education research in China, this paper adopts the literature research method to study the development of secondary vocational education in China. Firstly, we searched the literature of secondary vocational education research and found that the main research literature was focused on three areas: